DOF transcription factors: Specific regulators of plant biological processes - Zou, Xiaoman; Sun, Hongmei (Frontiers in Plant Science, 2023)
Plant biological processes, such as growth and metabolism, hormone signal transduction, and stress responses, are affected by gene transcriptional regulation. As gene expression regulators, transcription factors activate or inhibit target gene transcription by directly binding to downstream promoter elements. DOF (DNA binding with One Finger) is a classic transcription factor family exclusive to plants that is characterized by its single zinc finger structure. With breakthroughs in taxonomic studies of different species in recent years, many DOF members have been reported to play vital roles throughout the plant life cycle. They are not only involved in regulating hormone signals and various biotic or abiotic stress responses but are also reported to regulate many plant biological processes, such as dormancy, tissue differentiation, carbon and nitrogen assimilation, and carbohydrate metabolism. Nevertheless, some outstanding issues remain. This article mainly reviews the origin and evolution, protein structure, and functions of DOF members reported in studies published in many fields to clarify the direction for future research on DOF transcription factors.